Strategi Orang Tua dalam Meningkatkan Kreativitas Anak Usia Dini - Nailatur Rizqiyah; Masti Yanto; Moh Elman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Creativity is an important ability that needs to be developed from an early age. This article aims to explore various strategies used by parents to stimulate the creativity of their young children. The research method involves interviews and literature study to collect data. The results showed that parents adopted a variety of strategies to enhance their children's creativity. Some commonly used strategies include providing free play time, providing creative materials and equipment, and providing positive support and encouragement. Apart from that, parents also often support the exploration of their children's creative interests and talents. This research highlights the important role of parents in stimulating early childhood creativity and provides insight into effective practices in achieving this goal.